Letramento literário : materiais didáticos e o ensino da literatura - Soares, Samuel Ronobo (2008)
The main purpose of this work was to trace the orientations and literary literacy models in pedagogic materials and materials that also make the mediation of the literary text. The concept of literacy can be understood, herein, as a set of social practices that use the writing as a symbolic system and that use these practices with specific purposes and in specific contexts. Literature is seen as a type of specific writing that is different from all the other types of writing. Thus, the concept of literacy is depicted as very pertinent for the analysis of some aspects such as the ways of production, reception and circulation of literature and, consequently, its teaching. The Content Analysis was chosen as the course of methodological study for this research and as the base to study the literary literacy models found in dydatic materials. The analysis of the corpus comprised the dydatic materials from the first and eighth grades of the primary school, from the third year of high school, summaries of the books sent by the editors, internet sites and reading sheets. Based on the data, it was possible to make evident that the corpus presents an ambivalence regarding the literature teaching. Sites and specilized dydatic materials promote the critic discourse still developed by a bourgeois public, normally white and eurocentric. No interpretative possibility is given to readers since the materials mentioned above provide them with the ways of reading the texts. The ideas and the commentaries about the literary texts and the summmaries are available to the readers who want to interact about the fact. On the other hand, it is observed the search for other literary forms found in other resources. Therefore, it is noticed a predominance of the autonomous model of literary literacy which foresees that the meaning resides only in the text, desconsidering the context for the production of meanings. It is also observed, in the scope of dydatic materials here examined, a limitations of types of knowledge on literature, restricting its importance to literary periods, to the hystoric context, to the style characteristics, to main authors, types of characters and textual structures.